Cross-Border Cooperation on Migration: Human Security Perspectives in the EU and Ukraine - Arswenda Kusuma, Arnold; Irene Andalia, Carolina (Jurnal Ilmu Hubungan Internasional LINO, 2025)
Abstract: The recent flow of Ukrainian migrants in Europe has heightened the focus on human security in the aftermath of the conflict between Ukraine and Russia. Human security for Ukrainian migrants encompasses a wide range of needs, including migrant safety, economic stability, access to health services, and social needs. Furthermore, for Ukrainian migrants, human development includes not only survival needs but also the development of long-term opportunities for education, professional growth, and community integration. The issue of human security becomes important by examining how human security policies in European Union governments meet the basic needs of migrants and refugees. The focus of human security is on individuals, not on the state's foreign and security policies. By utilizing the concept of human security, this article seeks to analyse and see to what extent the EU has implemented human security, human rights, and human development in dealing with migrants from Ukraine.